Empowering Perinatal Mothers to Reduce Pain in Pregnant and Birthing Mothers through Birthing Ball Preparation Educationn - Rahayu, Wahyuni; Dewi Mayangsari (Nuban Jaggadhita Center, 2024)
Purpose: This community service activity aims to reduce pain in pregnant and labouring women after birthing ball. Methodology: The methods applied included hands-on training and mentoring by midwives and regular monitoring and evaluation at Puskesmas Purwoharjo Pemalang. This programme encourages families to motivate pregnant women to continue exercising to prepare for a baby's birth. A birthing ball is an exercise method for pregnant women to increase the well-being of mothers and babies. Findings: in the second and third trimester of pregnancy, pregnant women feel less back pain. Mothers entering labour have less pain during contractions. The family feels the well-being of the mother and baby